Nursing in the humanization of childbirth: an integrative literature review (Research, Society and Development, 2022)
Bibliographic study that sought to identify the scientific production on humanization and nursing care for vaginal delivery. The sources were scientific articles from the database of SCIELO-Brasil and VHL, period from 2015 to 2021. We obtained as search results 15 articles that were grouped into the following thematic areas: Humanized childbirth, nursing care, and humanization of care. Data analysis pointed out that the current paradigm is centered on childbirth intervention, despite the humanization movement defending natural and physiological childbirth. it is concluded that quality care is humanized during childbirth and birth privileges respect, dignity and autonomy of women, with the rescue of women's active childbirth in the parturition process.